2018
DOI: 10.1002/cpdd.461
|View full text |Cite
|
Sign up to set email alerts
|

Does Dapagliflozin Affect Energy Intake and Appetite? A Randomized, Controlled Exploratory Study in Healthy Subjects

Abstract: The primary aims of this study were to assess the effects of dapagliflozin versus placebo on energy intake and appetite ratings in healthy individuals. This was a randomized, single-blind, placebo-controlled, 2-period crossover study. In each period, healthy individuals received either dapagliflozin or placebo for 2 weeks. On assessment days, participants were asked to consume a standard preload breakfast. Appetite ratings were measured with 100-mm visual analog scales immediately before and during the 4.25-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In the current study, we extended the period of SGLT2 inhibition to 12 weeks and hypothesized that this longer duration of treatment would evoke measurable effects on dietary preferences, and hunger and appetite. Contrary to our hypothesis, and in agreement with the previous study [23], we observed no influence of SGLT2 inhibition on scores of hunger and appetite, and on eating behavior (i.e., no differences in quantities and types of food selected and ingested). Hyperphagia has been proposed as one of the mechanisms to explain lower than predicted weight loss (based on caloric loss mediated by glucosuria) reported during SGLT2 inhibition [51].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, we extended the period of SGLT2 inhibition to 12 weeks and hypothesized that this longer duration of treatment would evoke measurable effects on dietary preferences, and hunger and appetite. Contrary to our hypothesis, and in agreement with the previous study [23], we observed no influence of SGLT2 inhibition on scores of hunger and appetite, and on eating behavior (i.e., no differences in quantities and types of food selected and ingested). Hyperphagia has been proposed as one of the mechanisms to explain lower than predicted weight loss (based on caloric loss mediated by glucosuria) reported during SGLT2 inhibition [51].…”
Section: Discussionsupporting
confidence: 88%
“…We surmised that low carbohydrate absorption may be "sensed" and eventually lead to adaptation manifested as changes in eating behavior. In a recent study, the influence of short-term (2-weeks) SGLT2 inhibition on dietary preferences (i.e., increased desire for sweet foods) and appetite were quantified; no statistically significant effects were observed [23]. In the current study, we extended the period of SGLT2 inhibition to 12 weeks and hypothesized that this longer duration of treatment would evoke measurable effects on dietary preferences, and hunger and appetite.…”
Section: Discussionmentioning
confidence: 83%
“…Dapagliflozin exerts beneficial effects (compared with placebo) on urinary albumin to creatinine ratio in patients with normo-, micro- or macroalbuminuria 41,6062. This effect is also seen in patients receiving angiotensin converting enzyme inhibitors or angiotensin receptor blockers 63.…”
Section: Effects Of Dapagliflozinmentioning
confidence: 99%
“…The proposed mechanisms for the cardioprotective and nephroprotective effects of dapagliflozin include64,65 (i) the improvement of hyperglycemia and insulin sensitivity, along with other metabolic effects such as uric acid reduction, (ii) the reduced inflammation, oxidative stress and oxygen‐consuming transport workload owing to reduced sodium and glucose reabsorption in the proximal renal tubules (indeed, it has been demonstrated that dapagliflozin may reduce proximal tubular cell injury),66,67 (iii) the blood pressure lowering effect, (iv) the increase in fasting glucagon,68 (v) the reduction in intraglomerular pressure owing to SGLT2 inhibition-induced increased sodium delivery to the macula densa, leading to constriction of afferent renal arterioles, (vi) the reduction of kidney fat deposition, which is considered ectopic fat that promotes diabetic kidney disease progression,60 (vii) the reversal of hypomagnesemia, which is correlated with a more rapid decline of renal function,69,70 (viii) the increase in erythropoietin levels that exhibits direct renoprotective effects,71 (ix) the increase in the production of ketone bodies, since they can be used as a more efficient energy substrate leading to reduction in renal hypoxia 72…”
Section: Effects Of Dapagliflozinmentioning
confidence: 99%
“…Therefore, dapagliflozin improves the glycaemic control in adults when combined with diet and exercise. By excreting the glucose in the urine, dapagliflozin leads to weight loss [4]. Dapagliflozin improves glycaemic control and prevents administration of increased doses of insulin in patients who cannot take metformin due to intolerance.…”
Section: Introductionmentioning
confidence: 99%